Algorithms for Searching the Shortest Path and Its Modification - N. I. Listopad; I. A. Karuk; A. A. Hayder (Цифровая трансформация, 2016)
The article presents an overview of the main trends and methods of searching the shortest path information transmission in the telecommunications networks. The basic algorithms and their modifications are described. Special attention is given to the modified Dijkstra's algorithm that takes into account QoS requirements. The modified algorithm and its UML diagram are presented.